2011
DOI: 10.1002/aoc.1806
|View full text |Cite
|
Sign up to set email alerts
|

ZrOCl2·8H2O as a highly efficient, eco‐friendly and recyclable Lewis acid catalyst for one‐pot synthesis of N‐substituted pyrroles under solvent‐free conditions at room temperature

Abstract: A new and efficient method for the synthesis of a variety of N-substituted pyrroles from condensation reactions of 2,5-hexanedione with amines or diamines using ZrOCl 2 ·8H 2 O as a water-tolerant Lewis acid catalyst at room temperature is described.The use of nontoxic, inexpensive, easily available and reusable catalyst under solvent-free conditions make this protocol practical, environmentally friendly and economically attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 67 publications
(36 reference statements)
1
5
0
1
Order By: Relevance
“…In continuation of our recent works on the preparation and use of polymeric Lewis acid catalysts in synthetic transformations , in this work we found that polystyrene‐supported gallium trichloride PS/GaCl 3 can be used as a stable, highly active, and reusable heterogeneous Lewis acid catalyst for the highly efficient o‐silylation of a variety of alcohols and phenols using readily available HMDS (Scheme ).…”
Section: Introductionmentioning
confidence: 68%
“…In continuation of our recent works on the preparation and use of polymeric Lewis acid catalysts in synthetic transformations , in this work we found that polystyrene‐supported gallium trichloride PS/GaCl 3 can be used as a stable, highly active, and reusable heterogeneous Lewis acid catalyst for the highly efficient o‐silylation of a variety of alcohols and phenols using readily available HMDS (Scheme ).…”
Section: Introductionmentioning
confidence: 68%
“…Among these approaches, the Paal-Knorr reaction is known as an extremely efficient pathway to produce pyrroles from primary amines and 1,4-dicarbonyl compounds under acidic conditions. Over the past decade, several typical acidic catalysts have been widely employed in the Paal-Knorr reaction including Lewis acids, [24][25][26][27][28] metal-organic frameworks, 29 deep eutectic solvents, 30 Brønsted acids. 31,32 Despite the potential utility of these catalysts, many of them still suffer from certain drawbacks, including long reaction times, volatile organic solvents, low yields, expensive and unrecyclable catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Recently, ZrOCl 2 ·8H 2 O has attracted much attention as catalysts in organic synthesis. Due to its easy availability, low costs, moisture stability, and low toxicity, ZrOCl 2 ·8H 2 O is effectively used as a green catalyst in organic reactions, such as synthesis of functionalized piperidine scaffolds, [34] synthesis of 5-amino-1-aryl-1H-tetrazoles, [35] synthesis of bis-β-amino ketones, [36] synthesis of homoallylic alcohols and amines, [37] synthesis of enaminones and enamino esters, [38] synthesis of N-substituted pyrroles, [39] synthesis of α-aminophosphonates, [40] synthesis of 2-substituted benzothiazoles, [41] synthesis of 3,4-dihydropyrimidin-2(1H)-ones, [42] synthesis of 1,8-dioxo-octahydroxanthene, [43] synthesis of imidazolines and bisimidazolines, [44] synthesis of 2-aryloxazolines and bisoxazolines, [45] synthesis of isobenzofuran-1(3H)-ones, [46] synthesis of β-acetamido ketones, [47] synthesis of hexahydroquinoline derivatives, [48] synthesis of αaminonitriles, [49] N-acylation of lactams, [50] synthesis of Nsubstituted pyrrole derivatives. [51] Nowadays, multicomponent reactions (MCRs) have received special attention in organic synthesis as they can produce target products in a single operation without isolating the intermediates and thus reducing the reaction times and energy.…”
Section: Introductionmentioning
confidence: 99%